Family function and life satisfaction of postgraduate medical students during the COVID-19 pandemic: the mediating role of meaning in life and depression. Issue 4 (April 2022) - Huang, Zewen; Zhang, Lejun; Wang, Junyu; Xu, Lu; Wang, Tingting; Tang, Yan; Li, Yin; Guo, Ming; Xiong, Yipin; Wang, Wenying; Yang, Xialing; Yu, Yifeng; et al.
Abstract: Recent studies have documented life satisfaction of people have changed during the COVID-19 pandemic. However, it is unknown about the influential factors and mechanisms of life satisfaction of postgraduate medical students during the COVID-19 pandemic. There is a strong link among life satisfaction and individual quality of life and achievement, so it is important to explore the influence mechanism of life satisfaction of postgraduate medical students and explore ways to improve life satisfaction for the development of postgraduate medical students. The current study was based on the Circumplex Model of Marital and Family System, The Theory of Family Functioning, The Meaning Maintenance Model, The Theory of Personal Meaning and Existential Theory to construct theoretical framework and examine whether meaning in life and depression would mediate the link between family function and postgraduate medical students' life satisfaction. By convenient sampling method, a total of 900 postgraduate medical students (Mage = 27.01 years, SD = 3.33) completed questionnaires including Family APGAR Scale, Chinese Version of Meaning In Life Questionnaire, Patient Health Questionnaire, and Satisfaction With Life Scale. In this study, SPSS 25.0 was used for correlation analysis, regression analysis and common method bias test, and AMOS 23.0 was used for structural equation modeling analysis. The results showed that (a) family function could predict life satisfaction of postgraduate medical students significantly; (b) both meaning in life and depression mediated the association between family function and life satisfaction in a parallel manner; (c) meaning in life and depression sequentially mediated the link between family function and life satisfaction of postgraduate medical students. The study illuminates the role of meaning in life and depression in improving life satisfaction and implies that it is necessary to focus on the changes of life satisfaction of postgraduate medical students during the COVID-19 pandemic, and medical educator can improve the sense of meaning in life of postgraduate medical students through improving their family function, further decreasing the risk of depression, finally improving their life satisfaction. Abstract : COVID-19 pandemic; Medical students; Life satisfaction; Family function; Meaning in Life; Depression.